Polish aesthetic discourse of the 20th century: interpretation of interpretations - E. I. Onishchenko, (Ukrainian Cultural Studies, 2018)
The article is devoted to the analysis of the Polish aesthetic discourse of the twentieth century and the prospects for its interpretation in the Ukrainian aesthetics, particularly in the works by Kateryna Shevchuk, defended at the department of ethics, aesthetics and culture studies of Taras Shevchenko National University of Kyiv. These research greatly extend the idea of the aesthetic canon of the Polish thought, classically represented by the aesthetics R. Ingarden and W. Tatarkiewicz and reveal the names of virtually unknown in Ukraine Polish scientists, including special interest is the legacy of L. Blaustein, M. Wallis, H. Elzenberg and G. Ossowski. In particular, this perspective covers traditional for the twentieth century aesthetics problems, including psychology of art, collective aesthetic experience, ratio, fantasy, and imagination. Also, new interpretive perspectives of sublime and ugly, aesthetical experience are opened. The theoretical orientations of the Polish scholars, in one way or another, were connected with the cornerstones of the aesthetic science - its subject, the conceptual-categorical apparatus, the structure of aesthetic consciousness, the phenomenon of artistic creativity, the specific nature of art, and others. In the process of conceptual concretization, in the field of Polish aesthetics a number of problems have been rather clearly distinguished, among which the special attention of practically all of its leading representatives has attracted the phenomenon of aesthetical experience. K. Shevchuk’s investigation opens up an opportunity, at least in the format of a secondary interpretation, to join the research of the Polish scholars, whose work proved to be a giant "white spot" for the Ukrainian aestheticians. Introducing actually unexplored concepts Polish scientists to the modern Ukrainian aesthetic theory not only facilitates the opening of "unknown pages" in the history of the twentieth century aesthetics, but also makes actual mark of new approaches to the analysis of classical problems, the relevance of which will never be a subject of doubt.
Keywords: interpretation, aesthetical experience, aesthetical feeling, emotion, fantasy, ugly, expression, stimulus